Education, Migration and Source Community Incomes in Rural China - Peter Karpestam (Lund University, School of Economics and Management, Department of Economics, 2011)
Residents in rural China doubt the benefits from education, yet there is empirical evidence supporting positive effects in urban and rural areas. This paper investigates whether education affects a variety of income attainment indicators for households in rural China, using a household survey from the provinces of Hebei and Liaoning. The analysis estimates education effects for household residents, but also for temporary migrants (rural-urban migrants) and children who have moved permanently (rural-rural migrants). This can help to answer a set of three related questions: 1) Does household welfare in rural China depend on education? 2) Is the effect of education contingent on the decision to migrate? and 3) Does education have dissimilar effect for rural-urban and rural-rural migrants? The results support that education has positive income effects and that migration yields no additional payoffs. However, there is no evidence that households benefit from higher education if migration is only temporary. Altogether, this signals positive payoffs of educational expenses to rural households but households which consider sending a migrant into the urban labor force are better off if the more educated stay at home.
Keywords: D13; F24; I20; J60; R23; 330; East Asia; China; Education; Migration; Remittances; Non-Farm Incomes